1999
DOI: 10.1063/1.125064
|View full text |Cite
|
Sign up to set email alerts
|

Microphotoluminescence mapping of packaging-induced stress distribution in high-power AlGaAs laser diodes

Abstract: Spatially resolved photoluminescence line scans were performed to determine the local stresses in AlGaAs laser diodes designed for high-power operation at 808 nm. In this approach, the sign and magnitude of the local stress are deduced from the spectral shift of the peak associated with band-to-band transitions in the n-type GaAs substrate. The sensitivity of the technique (minimal equivalent hydrostatic stress that can be detected) can reach 10 MPa or better. Correlations between solder-induced stress distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…Inhomogeneouspackaging induced strain has often been related to faster bar degradation. 15 Figure 1͑c͒ shows that the shift in the PL transition energy of the substrate is very small ͑Ͻ0.3 nm or 0.5 meV͒ across the red-emitting bars. This indicates that the packaging-induced strain of the unaged 650 nm laser bars is low and homogeneous.…”
mentioning
confidence: 96%
“…Inhomogeneouspackaging induced strain has often been related to faster bar degradation. 15 Figure 1͑c͒ shows that the shift in the PL transition energy of the substrate is very small ͑Ͻ0.3 nm or 0.5 meV͒ across the red-emitting bars. This indicates that the packaging-induced strain of the unaged 650 nm laser bars is low and homogeneous.…”
mentioning
confidence: 96%
“…The holder is designed to hold six standard 25-mm-diameter bandpass filters. Initial tests with this holder indicated that images taken with different order-sorting filters were sometimes shifted in position by up to 20 (for a field of view of ). This was caused, in part, by the misalignment of the individual filters with respect to the optical axis.…”
Section: Methodsmentioning
confidence: 99%
“…One significant factor affecting device reliability is the packaging-induced mechanical stress caused during the soldering of a laser bar to a heatsink [17]- [19]. This process can introduce an inhomogeneous strain profile across a device [20], which plays a role in defect formation. There are indications that degradation rates have a nonlinear dependence upon packaging induced strain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the expected strain distributions for standard packaging techniques such as soft soldering (typically with In solder on Cu heat sinks) or hard soldering (typically with AuSn solder on expansionmatched 1 heat sinks) are well known; see Refs. [4][5][6].…”
mentioning
confidence: 98%